PENGARUH KOMPETENSI, KEPUASAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS LINGKUNGAN HIDUP PEMKO BATAM - Sabri Sabri (EQUILIBIRIA, 2019)
This study aims to determine and analyze the influence of competence, job satisfaction and work environment on the performance of employees at the office of the environmental services of the Batam government. This study with a population of 95 people with sampling according to the provisions if the population under 100 samples is the entire population, with variables namely: variable Competence (X1), Job Satisfaction (X2), and Work Environment (X3) and Employee Performance (Y) .               The data analysis method used is multiple linear regression analysis which aims to determine the correlation between two variables, namely the independent variable and the depandent variable. Hypothesis testing is done by F Test and R2 Test (coefficient of determination). Analyzing data using the help of statistical data processing software, SPSS version 19.               The results show that this table shows the value of the Determination Coefficient which is used to determine the percentage of the dependent variable, in this case the Company Image which is calculated using the independent variables in the form of Competence (X1), Job Satisfaction (X2) and Work Environment ( X3) The Determination Coefficient is used to calculate the effect of the independent variable on the dependent variable. The Determination Coefficient is calculated by squaring the correlation results, then multiplying by 100%. The figure of R Square is the number of squared correlations or 0.9662 of 0.932. This R Square number is the Determination Coefficient. The value of the coefficient of determination is 0.932 or equal to 0.932 x 100% = 93.20%. This value means 93.20% Employee performance that occurs can be measured using competency variables (X1), Job Satisfaction (X2) and Work Environment (X3). While the remaining 6.80% must be explained by other factors. Keywords: Competence, job satisfaction, work environment, Employee Performance